Gestão Documental e de processos na implementação do Regulamento Geral de Proteção de Dados (RGPD): O caso iPortalDoc - Andreia Filipa Rajão Pinto (2018)
In this dissertation, developed under the Master in Information Science, the project developed in a business environment titled "Document and Processes Management in the implementation of the General Data Protection Regulation (GDPR): The iPortalDoc Case." is presented. The purpose of this theme is the development of an integrated solution in a Document and Process Management System, called iPortalDoc. In general, this solution was developed for three fundamental aspects: to support the organization's compliance with the new General Regulation on Data Protection; serve as a tool to support the Data Protection Officer and transform the bureaucratic process into a simpler and more innovative process. The theoretical study, referred to as a literature review, is considered the basis of the project, and so it was initially important to clarify the areas that support it: Information Management, Document Management and Personal Data Protection through a general for the specific about the new Regulation. Subsequently, a survey and an analysis of requirements were elaborated to understand how the RGPD could be implemented in IPBRICK. From there, the module was developed, called "IPBRICK RGPD Solution", which is organized by a set of folders, each folder composed of templates and workflows. In addition to the Module, a user manual has been produced that allows a more detailed view of how to complete the forms, their objectives and the workflow that each document follows. In conclusion, the development of this project led to the creation of a Module integrated in a Document Management System that has become a technological and innovative tool in the face of data protection.